(untitled) - Brown, William H. (Belmont, CA., 2005)
The text continues to build on its reputation of providing students with a progressive introduction to organic chemistry. One of the most outstanding features of the new edition is an increased and more thorough coverage of mechanisms. ORGANIC CHEMISTRY, fourth edition is clearly written and provides students with many more real life examples of organic chemistry, especially in the areas of bio-organic chemistry and medicinal chemistry.
Keywords: Chemistry, organic